A Simple Set of Rules for Characters and Place Recognition in French Novels - Bornet, Cyril; Kaplan, Frédéric (Frontiers in Digital Humanities, 2017)
This article describes a simple unsupervised system for automatic extraction and classification of named entities in French novels. The solution presented combines a set of different standalone classifiers within a meta-recognition system. The system is tested on 35 classic French novels, representing 5 million words and 3,700 names of people and places. The results demonstrate that although none of the standalone methods clearly outperforms the others, their combined classification offers a robust solution in this context.